Pesquisa em modelagem matemática no Brasil: A caminho de uma metacompreensão - Bicudo, Maria Aparecida Viggiani [UNESP]; Klüber, Tiago Emanuel (My University, 2011)
The purpose of this study was to analyze researches in mathematical modeling in the area of Mathematics Education in Brazil. Is was investigated the mathematical modeling papers published in the Proceedings of the Third International Seminar for Research in Mathematics Education - Sipem (2007). The phenomenological point of view was adopted, basing the interpretations on the hermeneutic movement, aiming move toward a metacomprehension about this topic. The core ideas emerge from the invariants articulated in the process of making convergences as, for example, the research which the primary focus was on the modes through which teachers work some topics of mathematical program employing the modeling recourse. These invariants may indicate weaknesses when the researches remain only in the how-to; but they may also point out new possibilities for understanding conceptions and their conversion in classroom practices.
Research in mathematical modeling in Brazil: The way for a metacomprehension
Keywords: Educational research; Hermeneutics; Mathematics education; Phenomenology